Unmet need for family planning among married women in Zambia: lessons from the 2018 Demographic and Health Survey - Harriet Namukoko; Rosemary Ndonyo Likwa; Twaambo E. Hamoonga; Million Phiri (BMC, 2022)
Abstract Background Unmet need for family planning among married women is still a public health concern in sub-Saharan Africa. In Zambia, one in every five married women had an unmet need for family planning in 2018. Unmet need for family planning has the potential to increase the number of unintended pregnancies and unsafe abortions. These factors can increase the proportion of women of child bearing age, who are at high risk of birth complications. This study was therefore conducted to understand the determinants of unmet need for family planning among married women in Zambia based on recent cross-sectional data. Methods The study analysed data extracted from the Zambia Demographic and Health Survey, which was a representative cross-sectional survey conducted in 2018. The analysis was done on a sample of 7598 currently married women aged 15-49 years. Multivariate logistic regression was used to examine determinants of unmet need for family planning in Zambia. The analyses was weighted to account for complex sample design. Results Prevalence of unmet need for family planning is still high in Zambia at 20%. Women in the age groups 25-34 and 35-49 were less likely to have total unmet need for family planning (AOR = 0.61; 95% CI 0.47, 0.78) and (AOR = 0.63; 95% CI 0.45, 0.86) respectively, compared with those aged 15-24 years. Age of a woman, parity, household wealth and exposure to media-based family planning messages were found to be significantly associated with unmet need for family planning among married women. Conclusion There were significant differences in unmet need for family planning based on a woman's age, number of children ever born, wealth level, and exposure to media-based family planning messaging. Improving access to family planning messages and addressing underlying structural factors that improve the wealth status, particularly among young women, may help to reduce unmet need for family planning in Zambia.